Pengembangan Lanjut Aplikasi Manajemen Persediaan Barang berbasis Android pada UMKM "Amira Shop" Ciganjur - Hilmy Saeful Fatah; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Currently, mobile applications have been used in various aspects by most people in supporting their daily lives, including the entrepreneurship process. However, technology-based recording is still very rarely found in medium to low scale businesses, one of which is the MSME Amira Shop. Therefore, we need an application that can automate the management of incoming and outgoing stock of goods. In the process of developing, this application using the waterfall process model. At the requirements analysis stage, 14 functional requirements and one non-functional requirement were found which were implemented in the form of use case diagrams and use case scenarios. Based on the results of the needs analysis, a system is designed in the form of sequence diagrams, class diagrams, and wireframe interfaces as the initial design of the application. At the implementation stage, the application design that has been compiled will be implemented in the form of mockups and applications that use the Kotlin language. And on the test results, functionality testing was carried out with perfect results. Usability testing was carried out using a task scenario with metrics of success rate, time-based efficiency and system usability scale which resulted in a score of 76%. Finally, the compatibility test got valid results on all tests with a minimum version of android 8.0 or Oreo.